Identifikasi Masalah Menggunakan Teknik Problem Check-List Pada Mahasiswa Program Studi Bimbingan dan Konseling Universitas Pattimura - Paul Arjanto (JKI (Jurnal Konseling Indonesia), 2015)
Counseling Study Program at Pattimura University in 2015/2016 academic year. The research variables are the problems faced by the students. The present research is a survey study. The data were collected through the instruments of Problem Check List (General DCM). Sampling technique using stratified random sampling. There were 315 students then by using Slovin`s formula we taken 177 students as a sample with error standart 5%. The data were analyzed using percentages. The results show that the students in general, still had some problems which inhibited them in their study completion. The problems needed to be solved. The problems were personal problems, physical and health, social relations, economic and financial problems, carrier and work, education and study, religious problems, value and moral problems, young couple relationship and marriage problems, family problems, and the problems related to their spare time.